Carbapenemasas KPC en Enterobacteriaceae aisladas en un Hospital de Maracaibo, Venezuela - Gómez-Gamboa Liliana; Perozo-Mena Armindo; Lugo Judith; Bermúdez-González José; Zabala Irene; Morales, Ever (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2014)
Abstract: Carbapenems have generally been considered the pharmacotherapy of last resort for managing infections associated with health services caused by multidrug-resistant gram-negative bacteria. However, it is worrisome that this situation is being threatened worldwide with the appearance of bacterial strains that resist these antibiotics due to the production of novel B-lactamases with direct carbapenem-hydrolyzing activity (carbapenemases). This study was performed to characterize KPC carbapenemase-producing Enterobacteriaceae isolated from a hospital in the Zulia region during 2009-2013. KPC carbapenemase production was detected in 423 strains of carbapenem-resistant Enterobacteriaceae (36.29%). The most affected patients were male adults from the intensive care unit. The most common site of colonization was the respiratory tract, while rectal carrier status was rare. These KPC carbapenemases were detected mainly in K. pneumoniae, K. oxytoca, E. coli and E. cloacae. Most isolates showed multidrug-resistance and an extensively drug-resistant phenotype. The majority of the phenotypic methods were effective for the detection of KPC producers in Enterobacteriaceae isolates and the presence of blaKPC gene confirmed that the Carbapenemase circulating in Enterobacteriaceae strains in this region are the KPC type. Resumen: Los antibióticos carbapenemes representan generalmente los últimos recursos para el tratamiento de infecciones asociadas a los servicios de salud producidas por bacterias Gram negativas multiresistentes. Es preocupante que esta situación esté siendo amenazada en todo el mundo por la aparición de cepas con resistencia a estos antibióticos debido a la producción de Carbapenemasas. Observando este panorama, se caracterizaron tanto fenotípica como genotípicamente las cepas de Enterobacteriaceae productoras de Carbapenemasas tipo KPC aisladas en un Hospital de la región Zuliana, durante 2009 a 2013. Fueron detectadas 423 cepas de Enterobacteriaceae resistentes a los carbapenemes debido a la producción de estas enzimas (36,29%). Los pacientes más afectados fueron adultos de sexo masculino procedentes de la Unidad de Terapia Intensiva. El sitio de colonización más frecuente fue el tracto respiratorio, mientras que el estado de portador rectal fue poco frecuente. Las KPC fueron detectadas principalmente en K. pneumoniae, K. oxytoca, E. coli y E. cloacae, siendo multidrogo-resistentes y extensamente drogo-resistentes. La mayoría de los métodos fenotípicos utilizados permitieron confirmar la presencia de Carbapenemasas y la detección del gen blaKPC confirmó que las carbapenemasas que circulan en cepas de Enterobacteriaceae de nuestra región son del tipo KPC.